The use of shape memory alloys in fuses for the protection of electrical installations - Kozyrskyi, V. V.; Nurek, T.; Sloma, J.; Bunko, V. Ya.; Goncharuk, M. V. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2026)
Problem. The degree of damage to electrical installations during short circuits depends on the response time of the protection. An effective way to enhance the current-limiting effect in electrical fuses (reducing their response time) may be the use of shape memory alloy (SMA) elements. However, this requires careful study and research. The goal of the work is to establish the patterns of strengthening the current-limiting effect of a fuse (reducing the response time) when using thermosensitive elements made of shape memory alloys. The achievement of this goal is based on the analysis of experimental studies conducted by the authors and mathematical models of the characteristics of a fuse containing an SMA element. Methodology. The article presents mathematical modelling of the parameters and characteristics of fuses with thermomechanical destruction of the fuse element, as well as a thermophysical model of a fuse with a thermosensitive SMA element. The article presents the results of experimental studies of a traditional fuse and a fuse equipped with a thermosensitive SMA element. For each current, the response time of the modified fuse was shorter than that of the traditional fuse. The use of a thermosensitive element reduced the response time by more than 20 times for a current of 10 A and approximately 10 times (from 0.257 s to 0.0244 s) for a current of 20 A. For the highest tested current (90 A), the fuse response time was half that of a traditional fuse. The article also presents the results of calculations of fuse characteristics using a mathematical model and a comparison with the results of experimental studies. Scientific novelty. The developed mathematical models of the characteristics of electrical fuses containing SMA elements made it possible for the first time to substantiate the interrelationships between the parameters (geometric dimensions and characteristics of SMA elements, fuse links) with current loads of electrical installations. The practical value of the work lies in the proposed use of thermosensitive elements made of functional materials to increase the current-limiting effect of electrical fuses for protecting electrical installations during short circuits. References 19, tables 2, figures 7.